A Novel Molecularly Imprinted Electrochemiluminescence Sensor Based on Mxene Quantum Dots for Selective Detection of Oseltamivir in Biological Samples - Wei Guo; Shiqiang Yan; Chaoqiang Xiao; Dayong Shi; Qing Hua; Xiaowen Hao; Wenjuan Zhang; Xuming Zhuang (Molecules)
Oseltamivir is a drug that has been widely used to prevent and treat influenza A and B. In this work, an ultrasensitive, simple, and novel electrochemiluminescence (ECL) sensor combined with molecularly imprinted polymers (MIP-ECL) based on a graphene-like two-dimensional material, Mxene quantum dots (MQDs) was constructed to selectively detect oseltamivir. A molecularly imprinted polymer membrane containing an oseltamivir template was constructed by electropolymerization and elution of modified MQDs on a glassy carbon electrode. Under optimized experimental conditions, the MIP-ECL sensor could detect oseltamivir in the range of 10−10 to 10−6 M (R2 = 0.9816), with a low limit of detection of 6.5 × 10−11 M (S/N = 3), and the recovery rates of oseltamivir in biological samples were 92.21–104.2%, with relative standard deviations of 3.70%~5.70%. The developed MIP-ECL sensor provides a new idea for detecting oseltamivir, which was successfully applied to the determination of oseltamivir in serum samples, indicating great potential for application in clinical diagnostics.